Pengaruh Harga, Jumlah Pengadaan dan Penyaluran Beras Terhadap Stok Beras di Perum Bulog Kantor Wilayah Jambi - Asmaida Asmaida; Suryadi Suryadi (Universitas Batangahari Jambi, 2023)
Perum BULOG is one form of SOE whose general business scope is in the field of food logistics, one of the commodities is rice. Rice is an agricultural product which is the basic need of the people of Jambi Province which is the highest source of carbohydrates compared to other types of food. The purpose of the study is to describe the condition of rice stocks in Perum BULOG Jambi Regional Office and the variables that affect these rice stocks in the 2018-2021 time period. The analysis technique used is multiple linear regression analysis. The results showed that the development of rice stocks at Perum BULOG Jambi Regional Office in the 2018-2021 period showed fluctuating data and tended to decrease. Simultaneously, the variables of rice prices at the farmer level, rice prices at the merchant level, the amount of rice procurement from within, the amount of rice procurement from outside (imports), and rice distribution have a significant effect on rice stocks at Perum BULOG Jambi Regional Office in 2018-2021. Partially, rice price variables at the merchant level and rice distribution variables have a significantly negative effect on rice stocks at Perum BULOG Jambi Regional Office in 2018-2021, while rice price variables at the farmer level, rice procurement variables from outside (import), and rice procurement from inside do not have a significant effect on rice stocks at Perum BULOG Jambi Regional Office in 2018-2022.